The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1080/10937404.2013.876288
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of an Oral Reference Dose (RfD) for the Nonphthalate Alternative Plasticizer 1,2-Cyclohexane Dicarboxylic Acid, Di-Isononyl Ester (DINCH)

Abstract: 1,2-Cyclohexanedicarboxylic acid, 1,2-diisononylester (DINCH), a polyvinyl chloride plasticizer, has food, beverage, and medical device applications that may result in general population exposure. Although no apparent toxicity information in humans was identified, there is a substantial data set in lab animals to serve as the basis of hazard identification for DINCH. Target tissues associated with repeated dietary DINCH exposure in lab animals included liver, kidney, and thyroid and mammary glands. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 26 publications
1
34
0
3
Order By: Relevance
“…Rubin (1975) and Schulz et al (1975). Bhat et al (2014) reported what had been reviewed by the independent National Sanitation Foundation (NSF) Health advisory board and by regulatory bodies such as EFSA and NICNAS on the toxicology of Hexamoll ® DINCH ® . They all concluded that target organs from oral administration were the thyroid gland and the kidneys.…”
Section: Metabolite Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Rubin (1975) and Schulz et al (1975). Bhat et al (2014) reported what had been reviewed by the independent National Sanitation Foundation (NSF) Health advisory board and by regulatory bodies such as EFSA and NICNAS on the toxicology of Hexamoll ® DINCH ® . They all concluded that target organs from oral administration were the thyroid gland and the kidneys.…”
Section: Metabolite Determinationmentioning
confidence: 99%
“…The issues for substitution range from ease of "drop-in" to efficacy for blood storage. Hexamoll ® DINCH ® was developed as a substitute plasticizer for "sensitive" applications: it has a low toxicity; is not considered to be an endocrine-active substance (Furr et al, 2014); and has a low migration from PVC (Bhat et al, 2014). Oral exposure was associated in rats with induction of liver enzymes that are believed to have altered circulating thyroid gland hormones, resulting in an enlarged thyroid gland; this effect is a secondary mechanism that is not considered to be relevant for humans (European Food Safety Authority, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Zusammenfassende Darstellungen der relevanten toxikologischen Untersuchungen und ihre Bewertungen finden sich in dem Bericht der europäischen Behör-de für Lebensmittelsicherheit [16], in der Dokumentation der australischen Chemikalienbehörde (NICNAS) [19] sowie in der Publikation von Bath et al [20]. Die Verwendung von DINCH in Medizinprodukten wurde durch ein wissenschaftliches Expertengremium der EU Kommission bewertet [4].…”
Section: Allgemeines Toxikologisches Profilunclassified
“…Die 2-Generationen-Studie wurde sowohl von der EFSA [16] wie auch von Bhat et al [20] einer Neubewertung unterworfen (s. Kap. 5).…”
Section: Tab 3)unclassified
See 1 more Smart Citation